The valorization of graphite as a file document: an interdisciplinary approach between information literacy and complexity theory - Pinheiro dos Santos, Beatriz Rosa [UNESP]; Luz Fernandes, Myrella Vaenia da; Martins Damian, Ieda Pelogia; Albuquerque, Ana Cristina de (Univ Brasilia, Dept Ciencia Informacao, 2018)
The objective was to analyze whether information literacy and complexity theory can contribute to the valorization and institutionalization of graphite as a document that can be processed in public archives. A qualitative bibliographical research was carried out. The results demonstrated that the standard of information literacy, which corresponds to the need for reliable sources for effective access to information, justifies and supports the idea of graphitization as an archive document, since it will provide standard, liberating and lasting access to society who decide to use and access graphite documented in public archives. In addition, it is concluded that one of the principles of complex thinking reflected the fact that there is no escaping this process of institutionalization of graphite, because this is a design of society, is an effect of some cause and configures moments of the history of the country and of the people.
Keywords: Graphite; Information literacy; Public Archives; Theory of Complexity